ATERRO SANITÁRIO CONSIDERAÇÕES SOBRE ESCOLHA DO SÍTIO, PROJETO, IMPLANTAÇÃO, OPERAÇÃO E MONITORAMENTO - Schalch, Valdir; Leite, W. C. de A.; Júnior, W. F.; Aguiar, E. M. de; Júnior, J. L. F. (Águas Subterrâneas, 1992)
INDISPONÍVEL